2009
DOI: 10.1107/s1600536809002001
|View full text |Cite
|
Sign up to set email alerts
|

catena-Poly[[diaquarubidium(I)](μ2-3-carboxypyrazine-2-carboxylato)(μ2-pyrazine-2,3-dicarboxylic acid)]

Abstract: The structural unit of the title compound, [Rb(C6H3N2O4)(C6H4N2O4)(H2O)2]n, consists of one rubidium cation, one hydrogen pyrazine-2,3-dicarboxyl­ate anion, one pyrazine-2,3-dicarboxylic acid mol­ecule and two water mol­ecules. This formulation is repeated twice in the asymmetric unit as the rubidium cation lies on an inversion centre. Each anion or acid mol­ecule is linked to two rubidium cations, while the rubidium cation has close contacts to four symmetry-equivalent organic ligands, with two different coor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2010
2010

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…For pyrazine-2,3-dicarboxamide, four Cu II structures (Mondal & Ray, 1977;Klein et al, 1983) with the ligand in an N,O-chelating mode and one Ag I structure (Massoud et al, 2009) with the ligand in an N:N 0 -bridging mode have been reported. In contrast, many compounds of pyrazine-2,3-dicarboxylic acid with alkali (Tombul et al, 2006(Tombul et al, , 2007Tombul, Gü ven & Bü yü kgü ngö r, 2008;Tombul, Gü ven & Svoboda, 2008;Tombul & Guven, 2009) and transition metals (Zou et al, 1998(Zou et al, , 1999Konar et al, 2004;Xu et al, 2008) have been synthesized and structurally characterized.…”
Section: Commentmentioning
confidence: 99%
“…For pyrazine-2,3-dicarboxamide, four Cu II structures (Mondal & Ray, 1977;Klein et al, 1983) with the ligand in an N,O-chelating mode and one Ag I structure (Massoud et al, 2009) with the ligand in an N:N 0 -bridging mode have been reported. In contrast, many compounds of pyrazine-2,3-dicarboxylic acid with alkali (Tombul et al, 2006(Tombul et al, , 2007Tombul, Gü ven & Bü yü kgü ngö r, 2008;Tombul, Gü ven & Svoboda, 2008;Tombul & Guven, 2009) and transition metals (Zou et al, 1998(Zou et al, , 1999Konar et al, 2004;Xu et al, 2008) have been synthesized and structurally characterized.…”
Section: Commentmentioning
confidence: 99%
“…For further information on pyrazine-2,3-dicarboxylic acid, see: Takusagawa & Shimada (1973); Richard et al (1973); Nepveu et al (1993). For further information on the synthesis of metal complexes with pyrazine-2,3-dicarboxylic acid ligand, see: Tombul & Gü ven (2009); Tombul et al (2006Tombul et al ( , 2007Tombul et al ( , 2008b. For a related structure of lithium with pyrazine-2,3-dicarboxylic acid ligand, see: Tombul et al (2008a).…”
Section: Related Literaturementioning
confidence: 99%
“…For related structures with the pyrazine-2,3-dicarboxylate (pzdc) dianion, see: Hua & Liu (2009); Konar et al (2004); Li et al (2004); Lin et al (2009); Tombul & Guven (2009); Wang et al (2008); Xiang et al (2004); Xu et al (2008).…”
Section: Related Literaturementioning
confidence: 99%
“…Di-and polycarboxylates are capable of bridging and providing effective magnetic exchange pathways. Pyrazine-2,3-dicarboxylic acid (H 2 pzdc) has been widely applied to construct polymeric coordination compounds; their structures and magnetic properties were investigated (Li et al, 2004;Xiang et al, 2004;Hua & Liu, 2009;Lin et al, 2009;Tombul & Guven, 2009). We present here the structure of the title compound, {[Cu(pzdc)(DMF)] .…”
Section: Data Collectionmentioning
confidence: 99%